Evaluation the Procedure for Recognition of Income Tax to Reduce Tax Evasion: بحث تطبيقي في الهيئة العامة للضرائب (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Tax state institution regards as one of the largest state institutions implementing the tax rules issuing be legislative body and achieving the goals of tax (financial, economic, social and political). So, the tax management should pay attention to the procedures enabling it to achieve those rules starting from the procedures of tax restrict and ending by tax allocation where the process of assessment the taxation must relaxing on modern methods. The problem of the study raising from that in spite of there is a low  obliging the taxable person (registered or not) to submit a declaration about his income and the achieved profit to be the base of taxation˒ where the other ways  are secondary ways helping in rejection of tax declaration, the scientific application becomes contravention of the law where  the tax declaration and its procedures transform to a secondary method effecting the tax obligation negatively and leading to the expansion of tax evasion beside that the is weakness in the procedures of taxation and in following up by the units which in charge of their achievement  all this lead us to the following question! Are the adopted procedures of taxation of true income and its resources achieved their role to restrict the tax erosion?  So, this study aims at shading the light on the theoretical framework of the tax declaration adopting in the tax state institution and its place among the different assessment methods, discussing the procedures of taxation depending on the income tax low, their abilities in retracting the tax evasion and the level of implementing of them by the responsible units, observing the weakness points, clearing the indicators of assessment and putting the solutions to treat them. The result of this study show that there are some weakness points in the procedures of taxation adopting by the responsible units in implementing them in the brings of the institution and in the process of following up by the department of vocational  and merchandise works. The study concludes some of suggestions basing on the scientific and theoretical conclusions among of them focusing on suitability of the tax procedure and don’t depending on the traditional desk inspection but trying to widen its field to include observation of the taxable person's records in their places of work .